AGAINST MEMORY DESPOLITIZATION. INTERVIEW WITH CARLOS ANTONIO ROJAS AGUIRRE: 40 YEARS AFTER MAY 68 - Correa Ramírez, John Jaime (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
On occasion of the 40 years after May 68 celebration, some lectures were given by international guests at Universidad Tecnológica de Pereira. Mexican historian Carlos Antonio Aguirre Rojas conducted an interview in which he extended his concepts regarding the historical significance of May 68, the persistence in the imagination of many student movements for the time being; at the same time, their different perceptions regarding the traditional historiography and the Zapatista movement in Mexico.